Baicalin-copper complex alleviates intestinal damage in avian pathogenic Escherichia coli-infected chicks by targeting the AKT/NF-κB pathway - Cao, Panpan; Wei, Jiazhen; Cheng, Xinyi; Zhuang, Yu; Luo, Junrong; Cao, Huabin; Zhang, Caiying; Guo, Xiaoquan; Hu, Guoliang (Frontiers in Veterinary Science, 2025)
BackgroundAvian pathogenic Escherichia coli (APEC), a primary bacterial pathogen in poultry, induces substantial economic losses to the global poultry industry. The baicalin-copper complex (BCU) demonstrates markedly potentiated anti-inflammatory, anti-oxidant, and anti-tumor efficacy relative to either baicalin or copper in their isolated forms. The present study aimed to evaluate the protective effects of BCU against APEC-induced intestinal damage in chicks.MethodsSeventy-five one-day-old chicks were randomly assigned to five groups: control group (basic diet), E. coli group (basic diet), and BCU treatment groups (10, 20, and 40mg/kg BCU). After a 15-day feeding period, APEC infection was induced via pectoralis injection to ensure consistent systemic infection. Two days later, the chicks were weighed, and blood samples from the pterygoid vein and ileum tissue were collected for subsequent experiments.ResultsThe results showed that compared with the E. coli group, BCU reduced both diarrhea and mortality rates, with reductions in the BCU40 group to 27% and 7%, respectively. It also significantly up-regulated the mRNA expression of key intestinal physical barrier proteins (ZO-1, ZO-2, Claudin-1, Claudin-3, and Occludin) and chemical barrier components (Mucin 2 (MUC2) and avian β-defensins (AvBD2, AvBD4) (p < 0.05). Compared with the E. coli group, as shown by BCU markedly increased activities of antioxidant enzymes GSH-Px, CAT, SOD and reduced MDA level, which along with increased mRNA expression of the Nrf2-antioxidant signaling pathway (p < 0.05). Furthermore, BCU significantly down-regulated the mRNA expression of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, IL-8, and significantly up-regulated the anti-inflammatory cytokines IL-10 and TGF-β (p < 0.05). Moreover, BCU inhibited the AKT/NF-κB signal pathway, as indicated by markedly reduced the protein expression of p-NF-κB and p-AKT (p < 0.01).ConclusionCollectively, the findings suggested that BCU effectively alleviates intestinal damage induced by APEC-infection through AKT/NF-κB signal pathway to modulate oxidative stress and inflammatory response.